Study on Leaching Pattern of Phosphate Glass Fertilizers with Different Compositions under Soxhlet Distillation Conditions - Tanmoy Das; Biswajit Mandal (Challenges and Advances in Chemical Science Vol. 7, 2021)
The objective of this study is related to the leaching study of the phosphate glass fertilizers with different compositions under Soxhlet distillation conditions. Glass fertilizers in the phosphate systems were melted at 900-950\(^°\)C with a soaking period of 1 h. Leaching study of these glasses with a maximum time period of 300 h was conducted under Soxhlet distillation condition with distilled water. Weight loss and the leach rates of the glass fertilizer samples were calculated from BET surface area measurements. They were in the range of 6.3x10-3 to 2.3x10-3 g.m-2.h-1 at 90\(^°\)C. The effect of different modifier ions like Na+, Fe3+, Mg2+, Ca2+, and K+ in the basic phosphate networks on melting and time of melting has been found to be evident. The pH determination ranging from 4.80 up to 7.50 of the leachate solution at ambient temperature under varying time intervals showed interesting and regular variations. The leaching study of such glasses under Soxhlet condition showed Ca2+, Mg2+, and K+ to be good candidates as modifier towards faster leaching. The findings have been corroborated in terms of ionic size, ionic radius, and hence the ionic potential of the modifier ions incorporated into the glass structure. The application of glass fertilizers was made on kharif paddy. The addition of alkaline earth oxides increases the corrosion of phosphate glasses, whereas the addition of intermediate oxides decreases the corrosion of phosphate glasses. It was shown that after the application of the glass fertilizer, the growth and production of the khariff paddy was better than the normal application of the conventional fertilizers.